Determinants of credit accessibility amongst small and micro enterprises in Kenya : A case study of Meru town - Ngumbi Avignon Mbiti (Meru : Avignon Mbiti Ngumbi, 2020)
In Kenya, SMEs are businesses employing between 1-50 people and may be either in formal or informal sectors and may also be in non-farm categories. Due to the sector importance, Kenta has enacted several laws in support of SMEs business, Which include and not limited to the MSME Act of 2011. The SMEs require concerted effort from both private and public since the sector draws stakeholders from both. To enhance their sustainability in economy, the SMEs require serious empirical research in order to elicit the constraints with the goal of developing proactive remedial frameworks so that their existence may be promoted. Amongst the numerous challenges that constrain the working of SMEs is inadequate financing, which leads to the overall goal of this study. The study variables were the lending procedures, credit awareness, collateral requirement and the interest rates to see whether and how they determine credit accessibility amongst the SMEs. Census was adopted as the study design informed by the small population and the ease of reaching the respondents. Location was Meru town. As per the Meru county government records, !60 SMEs are permitted and have been in operation for not less than 3 years. From every SME, one respondent was used. Descriptive research design was used. Questionnaire was used to collect data through a drop-pick method which was done in three days' time. Data analysis was through descriptive methods. Data analysis was done using SPSS version 22 by subjection to multiple regression to establish the existence of relatedness between the dependent and independent variables. Presentation of results was done through tables. Analysis done indicated the existence of correlation between the lending procedures; awareness of credit; necessities for guarantee and the interest charging. The analysis of variance results indicated the independent variables collectively had significant effect and informed recommendation for further study to be conducted to find out the other determinants of credit accessibility amongst SMES IN Kenya: a case of Meru town.